Synergy between loss of NF1 and overexpression of MYCN in neuroblastoma is mediated by the GAP-related domain - Shuning He; Marc R Mansour; Mark W Zimmerman; Dong Hyuk Ki; Hillary M Layden; Koshi Akahane; Evisa Gjini; Eric D de Groh; Antonio R Perez-Atayde; Shizhen Zhu; Jonathan A Epstein; A Thomas Look (eLife, 2016)
Earlier reports showed that hyperplasia of sympathoadrenal cell precursors during embryogenesis in Nf1-deficient mice is independent of Nf1’s role in down-modulating RAS-MAPK signaling. We demonstrate in zebrafish that nf1 loss leads to aberrant activation of RAS signaling in MYCN-induced neuroblastomas that arise in these precursors, and that the GTPase-activating protein (GAP)-related domain (GRD) is sufficient to suppress the acceleration of neuroblastoma in nf1-deficient fish, but not the hypertrophy of sympathoadrenal cells in nf1 mutant embryos. Thus, even though neuroblastoma is a classical “developmental tumor”, NF1 relies on a very different mechanism to suppress malignant transformation than it does to modulate normal neural crest cell growth. We also show marked synergy in tumor cell killing between MEK inhibitors (trametinib) and retinoids (isotretinoin) in primary nf1a-/- zebrafish neuroblastomas. Thus, our model system has considerable translational potential for investigating new strategies to improve the treatment of very high-risk neuroblastomas with aberrant RAS-MAPK activation.